Characterization of Glass Fiber / Epoxy with Various Silicone Resin Addition Composite’s Compressive and Flexural Strength - Muhamad Hananuputra Setianto; Herry Purnomo; Mochamad Chalid (Jurnal Sains Materi Indonesia, 2023)
Glass fiber/epoxy composite was developed and used widely in manyapplications. Development on fiber and matrix of composite material was done to improve itsproperties. Improvement of the composite’s matrix can be done/by adding a modifier. Silicone resinis one kind of modifier that can be added to epoxy to improve its properties. Silicone resin willimprove the thermal stability of epoxy, but the effect on mechanical properties, especially whencombined with glass fiber, has not been done. In this study, a composite of glass fiber/epoxy with 0,10, 20, and 30 weight-% silicone resin addition was tested by compressive and flexural loadingmethods. Compressive strength and maximum strain tend to decrease with the increase of siliconeresin added. The highest compressive strength and strain were reached by a glass fiber and epoxycomposite without any modification at the value 240.63 MPa and 0.5%. Flexural strength willdecrease, but maximum strain will increase when more silicone resin is added to the matrix on theflexural test. The biggest flexural strength at 293.73 MPa was possessed by the composite withoutfurther modification, and a maximum strain of 5% was owned by the composite with 20% and 30%silicone resin addition.